Sertraline inhibits stress-induced tumor growth through regulating CD8+ T cell-mediated anti-tumor immunity. Issue 9 (5th September 2022) - Zhou, Shuang; Ye, Di; Xia, Hongwei; Xu, Huanji; Tang, Weiping; Tang, Qiulin; Bi, Feng
Abstract : Chronic stress has been reported to be associated with tumor initiation and progression. But the underlying mechanism and the specific role of tumor immunity in this process are still unknown. Herein, we applied the repeated restrain stress model in C57BL/6J mice and found that the tumor growth in stressed mice was accelerated compared with that in control mice. In addition, serotonin, also called 5-hydroxytryptamine (5-HT), in the serum of stressed mice was also elevated. Sertraline, a selective serotonin reuptake inhibitor used in the clinic, can restore the serum 5-HT level in stressed mice and restrain tumor growth. We further explored the distribution of major immune cells, including B lymphocytes cells, T lymphocytes, natural killer cells, dendritic cells, tumor-associated macrophages (TAM) and regulatory T cells (Treg). We found that the infiltration of CD8 + T cells in the tumor microenvironment (TME) decreased significantly in stressed mice. And the extra 5-HT treatment could further decrease the infiltration of CD8 + T cells in the TME. The expression of IFN-γ and Granular enzyme B (GzmB) in CD8 + T cells were also dropped in the stressed mice group, whereas the expression of programmed cell death protein 1 (PD-1) on CD8 + T cells was increased. The T cell deficiency induced by stress can be reversed by sertraline, indicating its promising role in strengthening the efficacy of anti-PDL1/PD-1 immunotherapy. The present study provides new mechanistic insights into the impact of chronic stress on antitumor immunity and implicates a novel combined immunotherapy strategy for cancer patients with chronic stress.